Cross Madzhab Comparison of Fiqh as an Effort to Strengthen Religious Moderation in Islamic Religious Education - Shokhibul Mighfar; Muhammad Faidulloh Al Hasani; Muhammad Habib Kamil (Literacy: Journal of Education and Social Science, 2025)
Indonesian society is plural and requires an inclusive, tolerant, and balanced religious approach. A cross-madzhab comparative study of fiqh demonstrates that differences of opinion among Islamic scholars represent intellectual richness rather than sources of division, and can therefore foster religious moderation and prevent fanaticism. This study aims to analyze the role of cross-madzhab fiqh comparison in strengthening religious moderation within Islamic Religious Education. Using a qualitative library research approach, this study analyzes classical fiqh texts, contemporary scholarly works, and educational literature through thematic content analysis. The findings indicate that Islamic religious moderation emphasizes tolerance, openness, and justice, which can be strengthened in Islamic Religious Education through teacher exemplification, moderation-based curricula, value integration across learning materials, and dialogical-participatory learning methods. Cross-madzhab comparison is relevant in shaping moderate attitudes by enabling students to understand juristic differences proportionally, thus discouraging exclusive truth claims and fanaticism. This study contributes to Islamic education discourse by positioning cross-madzhab comparison as a pedagogical tool to strengthen students’ inclusive and moderate religious character in a multicultural society.